2018
DOI: 10.1016/j.jvs.2017.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Ambulation and functional outcome after major lower extremity amputation

Abstract: Patients should be counseled that <50% of patients receiving MLEAs are ambulatory after amputation. Educating patients about the deleterious effects of obesity on ambulatory status after MLEA may motivate patients to improve their level of fitness to achieve successful ambulation. Patients with an elevated mFI, patients with dementia, and those on dialysis should be considered for AKAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 25 publications
(27 reference statements)
3
54
0
2
Order By: Relevance
“…Impairment variables of THES, SLB, hip extension, RoM restriction, and waist circumference comprised modifiable variables that can be directly influenced by rehabilitation intervention. Nonmodifiable personal factors of age and number of comorbidities were included in the regression analyses, since both variables have been associated with a decline in mobility in people with LLA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment variables of THES, SLB, hip extension, RoM restriction, and waist circumference comprised modifiable variables that can be directly influenced by rehabilitation intervention. Nonmodifiable personal factors of age and number of comorbidities were included in the regression analyses, since both variables have been associated with a decline in mobility in people with LLA …”
Section: Discussionmentioning
confidence: 99%
“…Lower limb amputation (LLA) affects over 623 000 Americans, with a prevalence that is anticipated to double globally by 2050 . Impairing strength and balance, amputation burdens patients and can markedly inhibit their ability to traverse common environmental barriers . Although prostheses mitigate some barriers to ambulation, the problem is multifactorial and often different patients with similar amputations demonstrate varying prosthetic mobility.…”
Section: Introductionmentioning
confidence: 99%
“…112 Of a cohort of 256 major amputees, 90% of whom were below-knee, Chopra et al reported 46% ambulatory at one-year postoperative ambulation rate. 113 Large longitudinal analysis of diabetic amputees failed to identify an additional risk factor in amputees versus controls, suggesting the amputation and its impact on function is a risk factor itself (26203063). Even with early prosthetic fitting followed by aggressive rehabilitation, this population are often requiring near-max (80%) cardiorespiratory capacity to ambulate before additional energy costs (rates of oxygen uptake divided by maximum aerobic capacity) are incurred from biomechanical adaptation to prosthetic ambulation.…”
Section: Amputation Versus Reconstructionmentioning
confidence: 99%
“…When compared to age-matched counterparts, it is well established that individuals with lower limb loss exhibited significantly reduced physical function. 23,24 This loss of function has been generally attributed to the bodily structural changes inherent to amputation, but a number of studies showed that non-physical stressors disproportionately affected individuals with limb loss. For example, a prognostic study by Melcer et al 25 showed that patients with limb loss exhibited significantly greater odds of mental health disorders even when compared to those with severe lower extremity trauma but not amputation at comparable disability levels.…”
Section: Discussionmentioning
confidence: 99%